The Relationship between Cross-Cultural Competence and Self-Adjustment in Migrant Students - Erika Devi Pakan; Maria Nugraheni Mardi Rahayu (Department of Guidance and Counseling, FIP, Undiksha, 2023)
The difficulty of adapting to a new environment means that some early adult individuals, such as students, need good relationships in learning to adapt slowly to perceived differences. Due to cultural differences, new students need competencies or abilities to adapt to the cultural differences. Therefore, this research was conducted to determine the relationship between cross-cultural competence and adjustment in migrant students from South Sulawesi. This research is included in quantitative research with a correlation design. The subjects involved in this research were 102 students who had migrated to Salatiga, and the sampling technique used was snowball sampling. The research collected data using a psychological scale as a questionnaire, which will be distributed online via Google Forms. Data analysis used Pearson and Spearman correlation tests. The results of data analysis show that cross-cultural competence shows a significant positive relationship with the academic adjustment component (0.402) and the social adjustment component (0.527). Then, the personal-emotional adjustment component (0.318). Lastly, with the institutional attachment component (0.376). Cross-cultural competence has a relationship with self-adjustment. In this way, migrant students must prepare by studying their destination city, such as culture, weather, bureaucracy, and other things, to adjust more quickly and cope with the demands of a new place.